Design of a Two-Stage Controller for Balancing and Stabilizing the Furuta Pendulum - Sebastián David Pintor Ahumada; Camilo Esteban Pérez-Espíndola; Oscar Danilo Montoya Giraldo (Statistics, Optimization & Information Computing, 2025)
Control systems play a fundamental role in regulating variables within dynamic systems, enabling stability according to specific requirements such as response time, reference tracking, and disturbance rejection. This research aims to design a two-stage controller capable of stabilizing the Furuta Pendulum in its upright position. To achieve this, a model predictive control (MPC) strategy is implemented, combined with a swing-up and energy-based lifting technique, and applied to the physical QUANSER inverted pendulum system. The article presents the mathematical modeling process and its integration into the predictive control design. To evaluate performance, a comparison is made with a classic state feedback controller, also implemented on the same physical system. Both controllers are subjected to standardized reference and disturbance scenarios, allowing for a comprehensive performance comparison through graphical analysis and the ITAE performance index. The results highlight the superior performance of the model predictive controller in terms of speed, tracking accuracy, and steady-state error, particularly in scenarios that require controller switching - an advantage not provided by the state feedback approach.